Development of collagen/PVA composites patches for osteochondral defects using a green processing of ionic liquid - Iqbal, B. (Taylor and Francis Inc., 2018)
Osteochondral defects are still a big challenge for the surgeons because of good biocompatibility and higher mechanical strength requiring issues of the implants. In this study, different concentrations of collagen (dissolved in ionic liquid) up to 60 were blended with polyvinyl alcohol to prepare hydrogels of good mechanical strength, with the best biocompatibility and excellent fluid uptake ability. Ionic liquid was used as a green solvent for dissolution of collagen at a higher concentration as compared to other normal solvents. The prepared hydrogels were characterized with Fourier transform infrared spectroscopy (FTIR) which showed the characteristic peaks assigned to collagen and PVA. The surface morphology was investigated using scanning electron microscopy (SEM) which revealed homogeneity of the composite patches. Thermal gravimetric analysis (TGA) performed for samples show good thermal stabilities. Fluid uptake ability showed the massive uptake of fluid by the hydrogels. Biocompatibility was tested using hemolysis and MTT assay. Electrodynamic fatigue testing system was used for evaluating the mechanical properties and measured the tensile strength in the range of 2.4 to 8.5âMPa. The prepared osteochondral patches show good biocompatibility and mechanical properties. Â© 2018 Taylor & Francis